Pemanfaatan Metode Simple Additive Weighting dalam Sistem Pendukung Keputusan untuk Menentukan Siswa Berprestasi - Khiara Nurulita; Nurcahya Pradana Taufik Prakisya; Dwi Maryono (Faculty of Teacher Training and Education Universitas Sebelas Maret Surakarta, 2024)
⚠️Notice: This article has been identified as a duplicate publication of the following article published in another journal:Utilization Method Simple Additive Weighting in Decision Support Systems to Determine Outstanding Students Media Informasi Teknologi (MIT) (https://epublikasi.digitallinnovation.com/index.php/mit/article/view/189)Based on internal verification, the authors did not request withdrawal and did not notify the JIPTEK Editorial Office that the manuscript had been submitted to another journal. This constitutes a violation of publication ethics, particularly regarding simultaneous submission and redundant publication, as outlined by the Committee on Publication Ethics (COPE) and JIPTEK’s editorial policy.Accordingly, the Editorial Board declares this article as a duplicate publication. The article will remain available on the JIPTEK website to maintain the transparency and integrity of the scholarly record, accompanied by this official notice.The Editorial Board of JIPTEK reaffirms its commitment to upholding academic integrity and strongly urges all authors to adhere to ethical publication standards at all stages of the submission and publication process.